Green HRM and Employee Eco-Consciousness: Exploring the Mediating and Moderating Factors in Sustainability Behavior - Euis Sri Rahayu; Moh. Adrian; Muhamad Alwi (Management Analysis Journal, 2025)
This study aims to analyze the impact of Green Human Resource Management (GHRM) on Employee Green Behavior (EGB), mediated by Green Work Engagement (GWE) and moderated by Individual Green Values. GHRM plays a crucial role in encouraging employees to engage in environmentally friendly practices, yet its impact on EGB is not always consistent. Using a quantitative-explanatory approach, data were collected through questionnaires with a Likert scale distributed to 66 employees involved in sustainability programs at the resort. The results of this study indicate that GHRM and GWE can influence the EGB, GWE can mediates the relationship between GHRM and EGB, IGV can moderates the relationship between GHRM and EGB. Future studies are encouraged to examine the role of employee ambidexterity as a moderating factor in the relationship between GHRM and GWE on EGB. Moreover, it is recommended that future research adopts a longitudinal design and a mixed-methods approach to provide more in-depth insights into employee environmental behavior.